Perceived quality of padel users: adaptation and validation of the QPadel assessment tool - Fernández Martínez, Nicolás; Gálvez-Ruiz, Pablo; Gómez Chacón, Ramón; Lara-Bocanegra, Alejandro (Frontiers in Sports and Active Living, 2024)
IntroductionPadel is currently an emerging sport that has experienced significant growth, enjoying popularity and widespread accessibility among the population. However, the padel context lacks a tool to assess the perceived quality of users in padel facilities and sports services. This study aims to adapt and validate an evaluation tool based on a literature review.MethodsThe sample included 402 users (298 men and 104 women, predominantly a frequency of play of 1–2 days a week for 1–2 h) from clubs across the Andalusian Autonomous Community (South of Spain). Psychometric properties were evaluated using exploratory and confirmatory factor analysis, internal consistency through Cronbach's Alpha indicator and composite reliability, as well as convergent and discriminant validity, using the statistical software SPSS (v.22).ResultsThe findings demonstrated adequate psychometric properties in various analyses (exploratory and confirmatory factor analysis), showing both internal consistency and validity (convergent and discriminant).DiscussionThe QPadel tool represents a significant contribution and advancement in the academic literature, with potential positive impacts on decision-making for improving padel facilities and services, as well as enhancing competitiveness.